Steel slag aggregate in concrete: the effect of ageing on potentially expansive compounds - Frías, M.; San-José, J. T.; Vegas, I. (Materiales de Construcción, 2010)
Growing numbers of plants have sprung up in recent years to treat the electric arc furnace slag generated in scrap metal melting. When this by-product is separated, crushed and screened, it yields a granular material known as steel slag aggregate, which may be profitably used in the manufacture of commercial concrete. The feasibility of this application depends essentially on the volume stability of the resulting aggregate. The present paper discusses the potentially expansive compounds (Cl-, SO3, free CaO and free MgO) present in aggregate derived from different types of black slag during aggregate ageing. The aim is to establish optimal ageing conditions to ensure volume stability in steel slag aggregate. The findings showed that the slag analyzed had low concentrations of the expansive compounds studied and that possible swelling can be reduced by 45day ageing.